2016
DOI: 10.1016/j.yhbeh.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of treatments with 17β-estradiol and its brain-selective prodrug in a double-transgenic mouse model of Alzheimer's disease

Abstract: Estrogens are neuroprotective and, thus, potentially useful for the therapy of Alzheimer’s disease; however, clinical use of hormone therapy remains controversial due to adverse peripheral effects. The goal of this study was to investigate the benefits of treatment with 10β,17β-dihydroxyestra-1,4-dien-3-one (DHED), a brain-selective prodrug of 17β-estradiol, in comparison with the parent hormone using APPswe/PS1dE9 double transgenic mice to model the pathology of the disease. Ovariectomized and intact females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…In contrast, luteolin (9) itself reached only a F I G U R E 6 Cyclic antioxidant mechanism for estrone and estradiol, involving a chemically stable, p-quinol intermediate formed through • OH radical scavenging. DHED was successfully applied in vivo as a brain-targeted neuroprotective pro-drug of estradiol [147][148][149] HUNYADI | 2515 0.6 nM/mL peak plasma concentration in that study, and its concentration in the organs was also typically below that of 9c. 124 Unlike luteolin, its glycosides reach the large intestine where the sugar moieties can efficiently be cleaved by gut bacteria.…”
Section: Metabolism Of Luteolinmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, luteolin (9) itself reached only a F I G U R E 6 Cyclic antioxidant mechanism for estrone and estradiol, involving a chemically stable, p-quinol intermediate formed through • OH radical scavenging. DHED was successfully applied in vivo as a brain-targeted neuroprotective pro-drug of estradiol [147][148][149] HUNYADI | 2515 0.6 nM/mL peak plasma concentration in that study, and its concentration in the organs was also typically below that of 9c. 124 Unlike luteolin, its glycosides reach the large intestine where the sugar moieties can efficiently be cleaved by gut bacteria.…”
Section: Metabolism Of Luteolinmentioning
confidence: 89%
“…Prokai et al found that • OH radical scavenging by estrone yields a p ‐quinol A‐ring‐containing intermediate that subsequently undergoes a NADP‐dependent enzymatic reduction back to estrone, without contributing to oxidative stress on its own but becoming able to scavenge further radicals . In vivo administration of the analogous p ‐quinol derivative of estradiol (DHED) demonstrated no estrogenic activity, and it was rapidly taken up into the brain where it initiated the above‐mentioned redox cycle; therefore it acted as a targeted neuroprotective agent without any apparent systemic side‐effects . On one hand, this provides an attractive strategy to deliver estrogens to the brain through their pro‐drugs.…”
Section: Biological Significance Of Rons Scavenging‐related Antioxidamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, female CSF-E2 level is positively correlated with CSF-Aβ level and cerebral glucose metabolism in the left hippocampus PET scan, which denotes that they are at increased risk to develop AD. In short-term studies, transdermal estrogen administration is associated with increased attention, verbal and visual memories; however, long-term studies failed to slow down AD progression or adding benefits to rivastigmine therapy in postmenopausal women [47,81].…”
Section: Estrogens and Alzheimer's Diseasementioning
confidence: 99%